2015
DOI: 10.1111/den.12423
|View full text |Cite
|
Sign up to set email alerts
|

Obscure gastrointestinal bleeding: Diagnosis and treatment

Abstract: Small-bowel bleeding comprises a majority of obscure gastrointestinal bleeding, but is caused by various kinds of diseases. For its diagnosis, history-taking and physical examination is requisite, leading to a suspicion of what diseases are involved. Next, cross-sectional imaging such as computed tomography should be done, followed by the latest enteroscopy, videocapsule endoscopy and deep enteroscopy according to the severity of hemorrhage and patient conditions. After comprehensive diagnosis, medical, entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 68 publications
(141 reference statements)
1
37
0
2
Order By: Relevance
“…described that tarry stools were mostly of upper GI, jejunal, or ileal origins, whereas bright or dark red stools were often of ileal or colorectal origins. Although acute massive bleeding in the upper GI tract or bleeding of jejunal lesions causes reddish bloody stools, and a small volume of bleeding in ileal or colonic lesions causes black stools, especially in constipated patients, the color and properties of the stool are often considered helpful in predicting the locations of lesions . Complicated abdominal pain or distention suggests small‐intestinal invagination or stenosis as a result of tumors or inflammation, such as Crohn’s disease and intestinal tuberculosis.…”
Section: Diagnosismentioning
confidence: 99%
“…described that tarry stools were mostly of upper GI, jejunal, or ileal origins, whereas bright or dark red stools were often of ileal or colorectal origins. Although acute massive bleeding in the upper GI tract or bleeding of jejunal lesions causes reddish bloody stools, and a small volume of bleeding in ileal or colonic lesions causes black stools, especially in constipated patients, the color and properties of the stool are often considered helpful in predicting the locations of lesions . Complicated abdominal pain or distention suggests small‐intestinal invagination or stenosis as a result of tumors or inflammation, such as Crohn’s disease and intestinal tuberculosis.…”
Section: Diagnosismentioning
confidence: 99%
“…De acuerdo a la expresión clínica, la hemorragia gastrointestinal se clasifica en manifiesta y oculta, y según la localización se cataloga como alta y baja; esta es de origen oscuro cuando persiste o aparece el sangrado después de realizar endoscopia de vías digestivas altas y colonoscopia negativas (8). Con el advenimiento de técnicas endoscópicas y radiológicas que evalúan el intestino delgado, en los último años se ha propuesto la definición de sangrado probable de intestino delgado o sangrado gastrointestinal intermedio para los pacientes a quienes se realiza endoscopia digestiva alta y colonoscopia negativas, reservando el término sangrado de origen oscuro para los pacientes en quienes el origen de la hemorragia no se ha identificado posterior a realizar endoscopia digestiva alta, colonoscopia y estudios de intestino delgado como videocápsula endoscópica, enterografía por tomografía o resonancia magnética, angiografía, gammagrafía, enteroscopia de empuje, enteroscopia profunda con balón o en espiral, o enteroscopia intraoperatoria (9).…”
Section: Discussionunclassified
“…Robles et al (9) reported that the histological detection rate of GISTs by DBE biopsy was 71.4%. The first-line treatment for small intestinal GISTs with excessive bleeding remains debatable (10,11). The endoscopic treatment by DBE is very limited in massive GIST bleeding, but it may be possible, delaying or averting emergency surgery (9).…”
Section: Discussionmentioning
confidence: 99%